2001
DOI: 10.1093/aje/154.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Abdominal Aortic Aneurysms in a Population-based Study : The Tromso Study

Abstract: In a population-based study of 6,386 men and women aged 25--84 years in Tromsø, Norway, in 1994--1995, the authors assessed the age- and sex-specific distribution of the abdominal aortic diameter and the prevalence of and risk factors for abdominal aortic aneurysm. Renal and infrarenal aortic diameters were measured with ultrasound. The mean infrarenal aortic diameter increased with age. The increase was more pronounced in men than in women. The age-related increase in the median diameter was less than that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
422
8
32

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(487 citation statements)
references
References 32 publications
25
422
8
32
Order By: Relevance
“…A similar but much smaller Norwegian study of Ͼ6300 subjects (25 to 84 years of age) identified an AAA Ն3.5 cm in 8.9% of men and 2.2% of women. 29 Prevalences were low for both men and women Ͻ50 years of age but rose sharply and linearly for men Ͼ50 years of age and for women Ͼ60 years of age, albeit less steeply. 34 The presence of clinically silent atherosclerosis has most often been detected by screening x-ray examinations, computed tomography (CT), and echocardiography, particularly transesophageal echocardiography (TEE), which is regarded as the most sensitive technique for detecting clinically silent aortic atherosclerosis.…”
Section: Aortic Atherosclerotic Diseasementioning
confidence: 94%
“…A similar but much smaller Norwegian study of Ͼ6300 subjects (25 to 84 years of age) identified an AAA Ն3.5 cm in 8.9% of men and 2.2% of women. 29 Prevalences were low for both men and women Ͻ50 years of age but rose sharply and linearly for men Ͼ50 years of age and for women Ͼ60 years of age, albeit less steeply. 34 The presence of clinically silent atherosclerosis has most often been detected by screening x-ray examinations, computed tomography (CT), and echocardiography, particularly transesophageal echocardiography (TEE), which is regarded as the most sensitive technique for detecting clinically silent aortic atherosclerosis.…”
Section: Aortic Atherosclerotic Diseasementioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9][10][11] For women, the prevalence ranges from 0% in the youngest, to 5.2% in the oldest age groups. 1 Ruptured AAA causes approximately 9,000 deaths a year in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The typical initial treatment strategy includes the use of inotropic pharmacological agents and intra-aortic balloon pump (IABP) support but despite this mortality remains as high as 60%. [2] Therefore attention has turned to the use of ventricular assist devices (VAD), which are capable of restoring normal haemodynamics and organ perfusion even in the case of complete myocardial pump failure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AAA may show lower high-densitylipoproteins (HDL)-cholesterol levels and higher triglycerides concentrations [1], two lipid abnormalities usually accompanied by increased levels of small, dense LDL [2]. In fact, both the quality and the quantity of low-densitylipoproteins (LDL) seem to exert a direct influence on cardiovascular risk and LDL comprise multiple distinct subclasses with at least four major subspecies: large LDL-I, medium LDL-II, small LDL-III and very small LDL-IV [2].…”
Section: Introductionmentioning
confidence: 99%